2019
DOI: 10.15561/20755279.2019.0508
|View full text |Cite
|
Sign up to set email alerts
|

Circular training as a means for improving physical skills in future security specialists in higher education institutions of Ukraine

Abstract: Background and Study Aim. The battle training of military students is ineffective when limited to the knowledge of military equipment and ability to use it. The research theoretically and experimentally justifies how circular training can improve physical skills in future security specialists in HEIs of Ukraine. Material and Methods. The experiment involved a group of 7 respondents (aged between 21 and 23) of the Institute of the Department of State Guard of Ukraine. The methods of circular training were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Scientific reviews provide summary information that intervention studies are needed to promote and incorporate PT programs related to improvement or maintenance of physical fitness in police officers, which would result in health benefits and specifically improvement in performance of specific tasks of daily police work (Marins, David, & Del Vecchio, 2019). Our study revealed the positive impact of two additional supervised 16-week physical fitness training programs (mixed (jumping + strength endurance) workout and CrossFit training) on physical fitness and workability (Kolomiitseva et al, 2020;Pryimakov et al, 2019;Galimova et al, 2018). Nevertheless, in our opinion, these scientific data do not have a high level of evidence.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Scientific reviews provide summary information that intervention studies are needed to promote and incorporate PT programs related to improvement or maintenance of physical fitness in police officers, which would result in health benefits and specifically improvement in performance of specific tasks of daily police work (Marins, David, & Del Vecchio, 2019). Our study revealed the positive impact of two additional supervised 16-week physical fitness training programs (mixed (jumping + strength endurance) workout and CrossFit training) on physical fitness and workability (Kolomiitseva et al, 2020;Pryimakov et al, 2019;Galimova et al, 2018). Nevertheless, in our opinion, these scientific data do not have a high level of evidence.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies do not describe the methodology (Galimova et al, 2018), evidence-based statistics (Kokorev, Vyprikov, Bodrov, 2018), while other studies do not have requirements for sufficient number and physical fitness of participants. Some scientists have conducted studies with very few participants (less than 10 participants), which reduces the level of evidence (Pryimakov et al, 2019). Participants in our study had similar indicators of age, height, weight, and physical fitness to increase the level of evidence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Initially, CrossFit was considered an exercise system to improve physical condition, but soon it turned into a "fitness sport", representing a complex synthesis of several sports events or sports games [9,12,13,14]. CrossFit is a powerful motivation means for high-intensity functional training of young people [15,16,17], a means of increasing strength, aerobic and anaerobic capacities [17,18,19] and strengthening youth health [13,14]. Despite a sufficient number of works confirming the effectiveness of the CrossFit® system impact on the body of students [2,17,18,19], the studies of foreign and national (Ukrainian) authors lack a comparison of the efficiency of different youth physical training programs.…”
mentioning
confidence: 99%
“…CrossFit is a powerful motivation means for high-intensity functional training of young people [15,16,17], a means of increasing strength, aerobic and anaerobic capacities [17,18,19] and strengthening youth health [13,14]. Despite a sufficient number of works confirming the effectiveness of the CrossFit® system impact on the body of students [2,17,18,19], the studies of foreign and national (Ukrainian) authors lack a comparison of the efficiency of different youth physical training programs. The published works present scattered information on the impact of CrossFit means upon the components of the physical condition of the trainees -physical development, motor qualities, functional state, and health status [13,14,20].…”
mentioning
confidence: 99%